Penerapan Metode Cooperative Learning Dalam Rangka Meningkatkan Hasil Belajar IPS Bagi Siswa Kelas V SD Negeri 107 Seluma - Herawani, Titi (JURNAL ILMU PENDIDIKAN, 2022)
Research into this is the inclusive of researching into in the class V. Research into conducted in 2 cycle by subyek 39 student in the class V SDN 107 Seluma of]school year 2016/ 2017. Data of Result of researching into as follows : assess to flatten - flatten the result learn at cycle 1 is 69 and and in cycle II become 74,76, there is improvement 15,76. Complete student learn the pad cycle 1 only 23 student or 58% what its value reach the KKM, at cycle II become 35 student or 89,74%.Aktivitas cycle student 1 showing only 23 active student and in cycle II become 35 active student in study. Applying of Method of Cooperative Learning at Tribe items and Cultural is in Indonesian proven can improve the result learn the IPS of student of class of V SDN 107 Seluma of school year 2016 / 2017